METABOLIC AND HEMOSTATIC PARAMETERS IN PRE-DIABETES AND NEWLY DIAGNOSED TYPE 2 DIABETES - G. G. Petrik; E. D. Kosmacheva; A. V. Bratchik; R. O. Kudryashov; V. A. Glushanova (Российский кардиологический журнал)
Metabolic changes in diabetes mellitus are associated with hemostatic disorders. However, the sequence of hemostatic events in the early stages of disease remains unclear.Aim. To assess metabolic and hemostatic parameters and their interaction in pre-diabetes and newly diagnosed type 2 diabetes mellitus (ND T2DM).Material and methods. The study enrolled volunteers of 40 to 65 years who considered themselves healthy and did not get any medication therapy. Of 170 examined individuals, 46 had impaired carbohydrate exchange (ICE) — 13 with impaired fasting glucose, 17 — impaired glucose tolerance and 16 with ND T2DM. The control group comprised healthy volunteers with normal body mass index and without signs of metabolic abnormalities. The metabolic (carbohydrate, lipid, protein exchange, hepatic transaminase), platelet and plasma hemostatic parameters (mean platelet volume, ADP- &collagen-induced platelet aggregation, coagulation profile, fibrinogen, plasminogen) were investigated. We identified the peculiarities initiating impact of changed parameters on different hemostatic components in patients with pre-diabetes and ND T2DM.Results. Concentration of insulin, C-peptide, Homa-IR, total cholesterol demonstrated increase in groups with ICE. ADP-induced platelet aggregation, fibrinogen increased in ICE, however these changes were not statistically significant. Mean platelet volume and plasminogen had the tendency to be elevated in pre-diabetes and demonstrated significant increase in ND T2DM.Conclusion. Metabolic disorders in prediabetic stage initiate changes in platelet hemostasis and fibrinolysis. The increase of MPV and higher concentrations of plasminogen are considered to be significant in ND T2DM.